An Evaluation of the National Information Communication and Technology (ICT) Policy at the University of Namibia in the Faculty of Education. (January 2018) - Isaacs, Albert; Kazembe, Lawrence; Kazondovi, Collins
The purpose of this evaluation study was to determine the extent to which the teacher educators in the Faculty of Education at the University of Namibia implemented the national Information and Communication Technology (ICT) Policy for Education. This study employed both the quantitative method in the form of questionnaires and the qualitative method in the form of interviews and classroom observations. From the 100 participants surveyed, there were 73 respondents indicating a 73 per cent response rate to the questionnaire. The data were analysed by using the Likert Scale, Pearson-Product Moment Correlation Coefficient, Eigenvalue: Factor Analysis and Eigenvalue: Cluster. A purposive sampling was then conducted on the teacher educators at University of Namibia campus who were tasked to teach with ICTs. These teacher educators were interviewed and classroom observations were conducted. The findings of the study indicated that the participants had a good understanding of the national ICT Policy for Education. A majority of the teacher educators indicated that they were at the beginning level of using ICTs for teaching. They mainly used word processors and presentation tools for the purpose. However, the findings further indicated that the respondents lacked training in ICT pedagogy, lacked the time to learn and incorporate ICT skills and tools into lessons, and exposed insufficient budget allocation in place for procurement of ICT tools such as hardware and software.